Chromosome-level genome assembly of Malus niedzwetzkyana, the mother of Rosybloom crabapple - Ruizhen Wang; Jian Quan; Boyang Liu; Yu Wei; Hengxing Liu; Ran He; Ling Guo; Leiming Dong (Scientific Data)
Abstract Malus niedzwetzkyana (MN) is the mother of Rosybloom hybrids, ornamental crabapples with red and purple flowers. We present a high-quality chromosome-scale genome for MN with a size of 672.64 Mb, anchored to 17 chromosomes and with a high BUSCO completeness score of 98.6%, reaching the ‘gold standard’ level. Moreover, our assembly has captured 28 telomeres. A total of 43,813 protein-coding genes was annotated in the MN genome. The assembled high quality provides a valuable opportunity to enhance our understanding of the genetic basis of flower colour and other ornamental traits in crabapples, thereby advancing the field of genetics and breeding.